Applied Linguistics in Nepalese Academia: Historical Development, Contemporary Trends and Perspectives - Adhikari, Bal Ram (Education and Development, 2019)
Theoretical in its orientation, this article briefly surveys the historical development of applied linguistics, and its contemporary trends and perspectives in Western academia. Against this backdrop, it sheds light on the present situation of the discipline in Nepalese academia whereby its presence as an independent field of inquiry is yet to be realized. The article shows how the practice of applied linguistics in Nepal is confined to ‘linguistics applied’ and how the field has been subservient to linguistics and language teaching. Finally, it appeals for the practice of applied linguistics rather than merely linguistics applied in line with post-realities such as post-structuralism so as to address the language-related issues in the Nepalese society.